Lessons for Effective resilience programs: a case study of the RAIN pr ogram in Ethiopia - Kleiman, Shanti (Mercy Corps, 2013)
The RAIN program experience affirms the importance of multi-year and f lexible funding as key program design features if progress in resilien ce building is to be supported in areas with high levels of structural and temporal vulnerability. These features enable management to respo nd effectively to changing circumstances in order to better meet the n eeds of communities and to create the necessary conditions for relief- to-development strategies to take hold. Finally, this study found that deliberate and effective coordination between donor agencies can ensu re that development gains achieved during one program period are direc tly leveraged by subsequent programs, thereby increasing the effective ness of resilience programs.